2019
DOI: 10.17219/acem/110317
|View full text |Cite
|
Sign up to set email alerts
|

eGFR values and selected renal urine biomarkers in preterm neonates with uncomplicated clinical course

Abstract: Background. Diagnosing acute kidney injury (AKI) in preterm newborns, who are particularly susceptible to renal damage, is a serious challenge as there is no definite consensus about the diagnostic criteria. Objectives. The objective of this study was to measure the values for selected urinary biomarkers and estimated glomerular filtration rate (eGFR) among a population of preterm infants with uncomplicated clinical course as well as to determine whether these markers depend on birth weight (BW), gestational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
(80 reference statements)
1
8
0
Order By: Relevance
“…Moreover, the renal function parameters were also not different, similar to that of Miklaszewska et al. 27 Renal volumes correlate tightly with the body surface area, the relationship between renal volumes and body surface area never changes during childhood. 13 Renal volume z- scores are independent of age in childhood.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the renal function parameters were also not different, similar to that of Miklaszewska et al. 27 Renal volumes correlate tightly with the body surface area, the relationship between renal volumes and body surface area never changes during childhood. 13 Renal volume z- scores are independent of age in childhood.…”
Section: Discussionsupporting
confidence: 82%
“…Nonetheless, uNGAL/Cr ratio increases by 4.4% with a 1 day increase in post-natal age (95% CI: -5,6; (-3,2)). 26 We also found that the median protein intake received by participants at post-natal age 0-48 hours (2 (range: 0.72-3.48)) g/kg/day, 72 hours (3.12 (range: 0.87-4)) g/kg/day, and 21 days (3.44 (range: 2 -5.18)) g/kg/day were lower than our NICU guidelines. Even though the protein intake was lower than expected, the weight to age z-score (WAZ) at 21 days post-natal age according to the IPNG curve showed that 32 of 39 VPN had an increase in body weight compared to their birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…No pediatric nephrologist consultations were received from participants. Sepsis, nephrotoxic medication, and RD were recorded in26…”
mentioning
confidence: 99%
“…Nonetheless, uNGAL/Cr ratio increases by 4.4% with a 1 day increase in post-natal age (95% CI: -5,6; (-3,2)). 19 We also found that the median protein intake received by participants at post-natal age 0-48 hours (2 (range: 0.72-3.48)) g/kg/day, 72 hours (3.12 (range: 0.87-4)) g/kg/day, and 21 days (3.44 (range: 2-5.18)) g/kg/day were lower than our NICU guidelines. Even though the protein intake was lower than expected, the weight to age z-score (WAZ) at 21 days post-natal age according to the IPNG curve showed that 32 of 39 very preterm neonates had an increase in body weight compared to their birth weight.…”
Section: Discussionmentioning
confidence: 99%